Factores de riesgo y de protección y victimización por ciberacoso entre menores en Jerez de la Frontera: un estudio exploratorio = Risk and protective factors, and cyberbullying victimization among minors in Jerez de la Frontera: an exploratory study - Ganfornina, Ana María Ramírez (Behavior & Law Journal, 2020)
Minors are in a delicate situation with regard to the Internet, as they are vulnerable to multiple risks to which they are constantly exposed. In this investigation, a survey of 11 closed questions was carried out with a sample of 137 students from a high school in Jerez de la Frontera with the aim of analysing the probability of these minors to suffer a cyberbullying victimization, as well as to test if the victimization depends on risk behaviours and protection factors. The results allow us to conclude that children are exposed to a wide range of risk behaviours, but those that increase the probability of cyberbullying victimization are the number of hours they spend connected to Internet, the number of social networks in which they have a profile and the high and low risks. The protective factors we have identified to show an effect on cyberbullying victimization, with parents providing the most information about the Internet.